Clinical course and potential associated factors of progressive calcinosis cutis in early systemic sclerosis: a cohort study - Vassana Kanjanajarurat; Prathana Chowchuen; Chingching Foocharoen; Punthip Thammaroj (Annals of Medicine)
Background Calcinosis cutis of hands can progress and impair hand function in systemic sclerosis (SSc). Understanding the natural disease and comprehensive management is crucial.Objective To examine clinical course and identify risk factors associated with progressive calcinosis cutis in early SSc.Methods Dual time-point hand radiography was performed at initial and after diagnosis at median interval (range 2.9 ± 0.4 years) in 53 recruited patients with early SSc. Progressive calcinosis cutis defined as the worsening of severity according to simple soring scoring system (no, mild, moderate, severe) comparing to previous hand radiography. Odds ratio (OR) and their 95%CI were used to evaluate associated factors and calcinosis cutis progression.Results A total of 35 cases (155 per 100 person-year), showed progressive calcinosis cutis with the incidence of 22.6 per 100-person-years (95%CI 16.2–31.4). The most common area of progressive calcinosis cutis was at right distal phalanx, 12 of 35 (22.6%). Although statistically not significant by logistic regression analysis, elderly patients, Raynaud’s phenomenon, ischemic ulcer, telangiectasia, and salt-pepper tended to be more frequent in progressive calcinosis cutis than those who had no progression. Around one-quarter of those who had no calcinosis cutis experienced worsening across more than one level of severity.Conclusion Progression of calcinosis cutis in early SSc increased over time, particularly within 3 years after the first evaluation. Elderly patients and those with vasculopathy were found more frequently. Further study with a larger cohort is needed to support these findings.